The general optics structure of millimeter-wave imaging diagnostic on TOKAMAK. (8th January 2016) - Zhu, Y.; Xie, J.; Liu, W.D.; Luo, C.; Zhao, Z.; Chen, D.; Domier, C.W.; Jr., N.C. Luhmann; Chen, M.; Hu, X.
Abstract: Advanced imaging optics techniques have significantly improved the performance of millimeter-wave imaging diagnostics, such as Electron Cyclotron Emission imaging and Microwave Imaging of Reflectometry. The fundamental functions of millimeter-wave imaging optics are focusing, collecting the emission or reflected microwave signal from the target area in the plasma and focusing the emitted (reflected) signal on the detector array. The location of the observation area can be changed using the focus lens. Another important function of the imaging optics is zooming. The size of the observation area in poloidal direction can be adjusted by the zoom lenses and the poloidal spatial resolution is determined by the level of zoom. The field curvature adjustment lenses are employed to adjust the shape of the image plane in the poloidal direction to reduce crosstalk between neighboring channels. The incident angle on each channel is controlled using the specific surface type of the front-side lenses to increase the signal-to-noise ratio. All functions are decoupled with the minimum number of lenses. Successful applications are given.